Association of dietary patterns with diabetes-related comorbidities varies among diabetes endotypes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zhu, Anna; Zaharia, Oana-Patricia; Strom, Alexander; Bönhof, Gidon J.; Goletzke, Janina; Trenkamp, Sandra; Wagner, Robert; et al. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Choice architecture interventions promoting sustained healthier food choice and consumption by students in a secondary school setting: A systematic review of intervention studies - Schulte, Eva A.; Winkler, Gertrud; Brombach, Christine; Buyken, Anette (Public Health Nutrition)
Abstract Objective: To systematically review the impact of choice architecture interventions (CAI) on the food choice of healthy adolescents in a secondary school setting. Factors potentially contributing to the effectiveness of CAI types and numbers implemented and its long-term success were examined. Design: PUBMED and Web of Science were systematically searched in October 2021. Publications were included following predefined inclusion criteria and grouped according to number and duration of implemented interventions. Intervention impact was determined by systematic description of the reported quantitative changes in food choice and/or consumption. Intervention types were compared with regards to food selection and sustained effects either during or following the intervention. Setting: CAI on food choice of healthy adolescents in secondary schools. Participants: Not applicable Results: Fourteen studies were included; four randomized controlled trials and five each of controlled or uncontrolled pre-post design, respectively. Four studies implemented a single CAI type, with ten implementing > 1. Three studies investigated CAI effects over the course of a school year either by continuous or repeated data collection, while ten studies’ schools were visited on selected days during intervention. Twelve studies reported desired changes in overall food selection, yet effects were not always significant, and appeared less conclusive for longer term studies. Conclusions: This review found promising evidence that CAI can be effective in encouraging favorable food choices in healthy adolescents in a secondary school setting. However, further studies designed to evaluate complex interventions are needed.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).
Keywords: Nutrition and Dietetics; General Medicine; Medicine (miscellaneous)

Full Breastfeeding and Allergic Diseases—Long-Term Protection or Rebound Effects? - Libuda, Lars; Filipiak-Pittroff, Birgit; Standl, Marie; Schikowski, Tamara; von Berg, Andrea; Koletzko, Sibylle; Bauer, Carl-Peter; Heinrich, Joachim; Berdel, Dietrich; Gappa, Monika (Nutrients)
A previous follow-up of the GINIplus study showed that breastfeeding could protect against early eczema. However, effects diminished in adolescence, possibly indicating a “rebound effect” in breastfed children after initial protection. We evaluated the role of early eczema until three years of age on allergies until young adulthood and assessed whether early eczema modifies the association between breastfeeding and allergies. Data from GINIplus until 20-years of age (N = 4058) were considered. Information on atopic eczema, asthma, and rhinitis was based on reported physician’s diagnoses. Adjusted Odds Ratios (aOR) were modelled by using generalized estimating equations. Early eczema was associated with eczema (aORs = 3.2–14.4), asthma (aORs = 2.2–2.7), and rhinitis (aORs = 1.2–2.7) until young adulthood. For eczema, this association decreased with age (p-for-interaction = 0.002–0.006). Longitudinal models did not show associations between breastfeeding and the respective allergies from 5 to 20 years of age. Moreover, early eczema generally did not modify the association between milk feeding and allergies except for rhinitis in participants without family history of atopy. Early eczema strongly predicts allergies until young adulthood. While preventive effects of full breastfeeding on eczema in infants with family history of atopy does not persist until young adulthood, the hypothesis of a rebound effect after initial protection cannot be confirmed.
Keywords: Food Science; Nutrition and Dietetics

Perspective: A Conceptual Framework for Adaptive Personalized Nutrition Advice Systems - Renner, Britta; Buyken, Anette; Gedrich, Kurt; Lorkowski, Stefan; Watzl, Bernhard; Linseisen, Jakob; Daniel, Hannelore; Conrad, Johanna; Ferrario, Paola G.; Holzapfel, Christina; Leitzmann, Michael; Richter, Margrit; et al. (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Correction to: Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Abstract Purpose The COVID-19 pandemic and public measures have a direct impact on the nutrition situation; studies show changes in food consumption, eating behavior or body weight but complex pattern analyses of changes rarely exist. Methods During the first German lockdown, a web-based survey was conducted among adults. It included 33 questions about changes in food intake, eating habits and physical activity, as well as anthropometrics and sociodemographic factors. Patterns of change were calculated based on changes in food intake and eating habits using two-step cluster analysis. To identify influencing factors for assignment to the patterns of change, binary logistic regression analyses were performed. Results Data from 2103 participants (81% female, 40 ± 14 years) were considered for analysis. Increased stockpiling, cooking, and variation in preparation was reported by 50–70%. The constant pattern (C-P, 36%) reported little change besides the above. The health-oriented pattern (HO-P; 37%) reported eating more healthy foods, avoiding unhealthy foods, and eating less and less frequently. The emotional-driven pattern (ED-P; 28%) exhibits higher influence of emotions on eating behavior, less avoidance of unhealthy foods, and increased consumption of sweets, pastries, and alcohol. The odds of changing eating behavior either to HO-P or ED-P were higher in women, people with migration background, younger participants, and increased with BMI categories. Conclusion Both, the ED-P and HO-P, exhibit distinctive reactions in eating habits and food intake when dealing with a distressing experience. In subgroups, these may lead to disturbances in eating behavior and increase the risk for eating disorders and obesity.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Prospective association of family members’ sugar-sweetened beverages intake with children’s sugar-sweetened beverages consumption in China - Liu, Xue-Ting; Xiong, Jing-Yuan; Xu, Yu-Jie; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose We aimed to investigate whether parental and siblings’ sugar-sweetened beverage (SSB) intake had prospective impact on children’s SSB consumption, and the potential sex difference in these associations. Methods This study included a total of 904 children and their parents enrolled from 2004 to 2011 China Health and Nutrition Survey (CHNS) cohort study. SSB consumption information was estimated using a short dietary questionnaire and total energy intake was assessed with three-day 24-h dietary assessments at recruitment and follow-up surveys. Multivariate logistic or linear regression analyses were used to assess the association for SSB consumption between parents, siblings and children after adjusting for age, body mass index (BMI) z -score, household income and parental educational level. Results In this study, a majority (87.6%) of children consumed SSB. Among them, the median consumption of SSB was 70.3 ml/day per capita and 205.4 ml/day per consumer. Parental SSB consumption was relevant to children’s SSB consumption, and this association was more pronounced in boys than in girls. Meanwhile, fathers seemed to have a stronger impact on whether children consume SSB than mothers which was reflected by lower P and higher OR. Additionally, children’s SSB intake was prospectively associated with their older siblings’ SSB consumption ( P for trend < 0.03). Conclusions Parental and older siblings’ SSB consumption was relevant to children’s SSB intake. Particularly, boys were more susceptible to parental impact than girls, and fathers seemed to have a greater influence on children than mothers.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Maternal pregnancy weight or gestational weight gain and offspring's blood pressure: A systematic review - Ludwig-Walz, Helena; Nyasordzi, Juliana; Weber, Katharina S.; Buyken, Anette; Kroke, Anja (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Impact of lunch with carbohydrates differing in glycemic index on children's cognitive functioning in the late postprandial phase: a randomized crossover study - Drozdowska, Alina; Sinningen, Kathrin; Falkenstein, Michael; Rudolf, Henrik; Libuda, Lars; Buyken, Anette; Lücke, Thomas; Kersting, Mathilde (European Journal of Nutrition)
Abstract Purpose Studies about effects of lunch dietary Glycemic Index (GI) on cognition of schoolchildren are scarce. Our previous CogniDo GI study found no changes of cognition in the early postprandial phase after consumption of two rice types with medium vs. high dietary GI for lunch (i.e., 45 min after starting lunch). This study investigated whether the dietary GI of lunch has an impact on cognition of schoolchildren in the late postprandial phase, 90 min after lunch. Methods A randomized, 2 × 2 crossover intervention study was conducted at a comprehensive school with 5th and 6th grade students. Participants ( n = 212) were randomly assigned to either sequence 1 or 2. In the first period, participants of sequence 1 received a dish with high GI rice (GI: 79), those of sequence 2 with medium GI rice (GI: 64)—in the second period, 1 week later, vice versa. Computer-based cognitive testing was performed 90 min after lunch examining tonic alertness, visual search and task switching, and working memory. Treatment effects and treatment effects adjusted for estimated lunch glycemic load (GL) were analyzed using a linear mixed model. Results The selected cognitive parameters were not affected by the GI of lunch 90 min after lunch, neither after intention-to-treat nor in the per-protocol analysis. Adjustment for GL also did not change results. Conclusion The present study revealed no notable differences after the consumption of two rice types with medium vs. high dietary GI for lunch in children’s cognitive function in the late postprandial phase, 90 min after lunch. Clinical trial registration German Clinical Trials Register (DRKS00013597); date of registration: 16/04/2018, retrospectively registered.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Retrospektive Evaluation der Umsetzung einer klinikinternen Handlungsanweisung zur Ernährungstherapie von Intensivpatienten - Dresen, Ellen; Weißbrich, Carsten; Bühlmeier, Judith; Weisheit, Christina; Egert, Sarah; Putensen, Christian; Stehle, Peter (Aktuelle Ernährungsmedizin)
Zusammenfassung Hintergrund Die begleitende Ernährungstherapie von Intensivpatienten stellt eine besondere Herausforderung in der klinischen Routine dar und erfordert die Implementation von leitlinienbasierten Handlungsanweisungen. Methoden In einer retrospektiven Analyse wurde die Umsetzung der klinikinternen Handlungsanweisung zur Ernährung kritisch kranker Patienten (Gültigkeitszeitraum September 2013 bis Januar 2016) sowie der Anordnung zur Ernährungstherapie auf einer operativen Intensivstation des Universitätsklinikums Bonn an Daten des Ernährungsmanagements von 31 Langzeit-Intensivpatienten (7 Frauen; Alter: 60 ± 17 Jahre; BMI: 28 ± 10 kg/m2; Dauer des Intensivaufenthalts: 34 ± 16 Tage) evaluiert. Ausgewertet wurden Daten zur Initiation, zum Ablauf sowie zur Berechnung und Umsetzung der Energie- und Proteinzufuhr. Dazu wurden jeweils die im Stationsalltag angeordnete bzw. protokollierte Zufuhr, die protokollierte Zufuhr abzüglich Reflux sowie das retrospektiv beurteilte Ziel, welches durch die klinikinterne Handlungsanweisung indiziert war, miteinander verglichen (linear gemischtes Modell). Ergebnisse Mit der enteralen Ernährung wurde im Mittel an Tag 4 ± 3, mit der (supplementierenden) parenteralen an Tag 3 ± 3 begonnen. Die Energiezufuhr wurde mit Korrekturfaktoren als ein Vielfaches des Grundumsatzes nach Harris & Benedict berechnet. Der individuell verwendete Korrekturfaktor zur Berechnung der angeordneten Energiezufuhr wich über die gesamte Dauer des stationären Aufenthalts 0,1 ± 0,3 vom retrospektiv als angemessen erachteten Korrekturfaktor ab. Hieraus resultierte eine Abweichung der angeordneten Energiezufuhr vom Energieziel von 123 ± 528 kcal/24 h. Insbesondere in den Tagen 1 – 10 betrug die Abweichung des angeordneten vom retrospektiv als angemessen erachteten Korrekturfaktor 0,2 ± 0,4, was zu einer Differenz zwischen angeordneter Energiezufuhr und Energieziel von 426 ± 772 kcal/24 h führte. Die protokollierte Proteinzufuhr lag über die gesamte Behandlungsdauer bei 1,1 g/kg KG/24 h, während das retrospektiv ermittelte Proteinziel 1,0 g/kg KG/24 h betrug. Schlussfolgerung Die Analyse liefert vertrauenswürdige Daten zur Implementation einer individualisierten Ernährungstherapie von Langzeit-Intensivpatienten auf einer operativen Intensivstation; diese können zur Weiterentwicklung von entsprechenden Handlungsanweisungen genutzt werden. Defizite bestehen sowohl im zeitlichen Ablauf (zu später Beginn) als auch in der Anordnung der Energie-/Nährstoffzufuhr. Umfassende Schulungen des ärztlichen und pflegerischen Personals zur Anwendung/Umsetzung der Ernährungstherapie sind zu empfehlen.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Alkalinization with potassium bicarbonate improves glutathione status and protein kinetics in young volunteers during 21-day bed rest - Biolo, Gianni; Di Girolamo, Filippo Giorgio; Heer, Martina; Sturma, Mariella; Mazzucco, Sara; Agostini, Francesco; Situlin, Roberta; Vinci, Pierandrea; Giordano, Mauro; Bühlmeier, Judith; Frings-Meuthen, Petra; Mearelli, Filippo; et al. (Clinical Nutrition)
Keywords: Critical Care and Intensive Care Medicine; Nutrition and Dietetics

Association between habitual coffee consumption and metabolic syndrome in type 1 diabetes - Stutz, Bianca; Ahola, A.J.; Harjutsalo, V.; Forsblom, C.; Groop, P.-H. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)